INTERNALIZATION OF SHARIA VALUES IN THE BUSINESS MODEL CANVAS OF 35 BANDUNG MOTORCYCLE RENTAL COMPANY - Nabiel karamy; Udin Saripudin (Journal of Management and Islamic Finance, 2024)
The increasing number of tourists in Bandung post-Covid-19 presents a strategic opportunity for companies providing motorbike rental services in the city. This opportunity requires a precise response from both established motorbike rental businesses and entrepreneurs looking to enter the motorbike rental industry. One appropriate response is the development of a well-thought-out business model to effectively capitalize on this opportunity. The use of the Business Model Canvas (BMC) as a tool for formulating the business model proves highly beneficial in crafting such a plan. This model is not only designed to maximize profits but also serves as a framework for internalizing Sharia values. Through qualitative methods, the research findings indicate that by internalizing Sharia values within the BMC, the Rental Motor 35 Bandung Company can create a sustainable and ethical business model that provides positive benefits not only to customers but also to the community and the environment. This alignment supports a business vision in line with Islamic ethical values.